Junior High School Students Creative Thinking Ability In Solving Open Ended Problems On Straight-Line Equations From Gender - Afni Molita; Masriyah Masriyah (Universitas Muhammadiyah Enrekang, 2023)
Teachers generally do not present exercises for students to think creatively because each exercise given is only result-oriented regardless of how the process is carried out by students. Therefore we need the right learning approach to improve students' creative thinking skills. An approach that can be used to improve students' creative thinking skills in learning is by providing open-ended questions. The purpose of this study was to obtain a description of (1) the mathematical creative thinking abilities of male students in solving open-ended questions on straight-line equations and (2) the mathematical creative thinking abilities of female students in solving open ended questions on straight line equations. This research method is descriptive qualitative. Data was collected using test methods and interview methods. The written test in this study was in the form of a Mathematical Ability Test (TKM) which was adapted from validated SMP National Exam questions with a selection of questions covering material for grades VII and VIII in odd semesters. Apart from that, the written test in this study was also a Problem-Solving Test (TPM) containing open-ended questions on straight-line equations. While the interview method was carried out after the students who were selected as research subjects took tests. The data collected was then analyzed qualitatively. The results showed that female students were only able to meet the fluency creative thinking ability indicators. However, female students did not meet the flexibility and novelty indicators. Thus, female students are included in the less creative category based on the level of students' mathematical creative thinking ability according to Siswono. Meanwhile, male students met the fluency and novelty mathematical creative thinking ability indicators. Thus, male students are included in the creative category based on the level of ability to think creatively mathematically according to Siswono.